Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Budaya Organisasi Sekolah terhadap Kinerja Guru - Maryani, Ani; Lian, Bukman; Wardarita, Ratu (Yayasan Sembilan Pemuda Indonesia, 2020)
This study aims to determine the effect of the principal's leadership style and school organizational culture on teacher performance. The research was conducted at the State Kindergarten in Ogan Ilir Regency. This type of research is descriptive quantitative. The sample in the study was 47 respondents with data collection techniques in the form of a questionnaire (questionnaire). The results showed that: 1) there is an effect of the principal's leadership style on teacher performance, 2) there is an influence of school organizational culture on teacher performance, 3) there is an influence between the principal's leadership style and school organizational culture on teacher performance.